The application of adat perpatih with regards to customary land ownership in Negeri Sembilan / Nora Ardilla Nordin, Norazalina Razali and Norzaliza Tesmin - Nordin, Nora Ardilla; Razali, Norazalina; Tesmin, Norzaliza (2007)
Adat Perpatih acts as a mirror which reflects the connection between the system of Adat and the Minangkabau community in Negeri Sembilan. Adat Perpatih was considered as a unique system of social since it contained the rules and regulations which act as a yardstick for the justification and legitimacy of certain conducts of society. Kuala Pilah and Rembau are the two districts in Negeri Sembilan that are still applying and practising Adat Perpatih. As mentioned earlier, this study looks into the application of Adat Perpatih in the land administration and ownership, and also to determine whether Adat Perpatih's land ysytem is still effective to cater the needs of modern society in Kuala Pilah and Rembau. Sometimes, the problems that arise with regards to Adat Perpatih actually come from the attitude of the society themselves who had failed to implement the rules of Adat Perpatih within their daily lives and dealings such as transfer, lease and charge. In fact, many of them have turned to a conventional system of dealings and administration, especially in land matters since customary rules was seen as obsolete and not suitable in our modern world. But, with the coming into force of Negeri Sembilan Land Enactment (Cap 215), customary land is put under the exclusive jurisdiction of the Negeri Sembilan State Council and also the Adat Chiefs such as Undang and Lembaga.